2019
DOI: 10.1080/14786419.2019.1597353
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharide and glucose esters from the roots of Polygala arillata

Abstract: The plant Polygala arillata has been used in the Oriental medicine as a tonic and for the treatment of certain diseases. Our current research on phytochemical profile of the roots of P. arillata led to the isolation of a new oligosaccharide ester (1), a new glucose ester (7), along with five known sucrose esters (2-6). Their structures were elucidated on the basis of extensive chemical and spectroscopic methods (NMR and MS spectra) as well as comparison with the literature data. To the best of our knowledge, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…As the obtained results, the purified compounds were divided into two groups—phenolic glycosides ( 1 - 9 ) and triterpenoid saponins ( 10 – 15 ). Many of these phenolic glycosides and triterpenoid saponins are commonly found in Polygala species, such as P. arillata [ 15 ], P. sibirica [ 16 ], and P. aureocauda [ 17 ]. However, this is the first report of compound 15 being isolated from the genus Polygala .…”
Section: Resultsmentioning
confidence: 99%
“…As the obtained results, the purified compounds were divided into two groups—phenolic glycosides ( 1 - 9 ) and triterpenoid saponins ( 10 – 15 ). Many of these phenolic glycosides and triterpenoid saponins are commonly found in Polygala species, such as P. arillata [ 15 ], P. sibirica [ 16 ], and P. aureocauda [ 17 ]. However, this is the first report of compound 15 being isolated from the genus Polygala .…”
Section: Resultsmentioning
confidence: 99%
“…Oligosaccharide ester is a class of biologically active compositions of P tenuifolia , which has neuroprotective and antidepressant effects [ 23 ]. Recent studies have shown that oligosaccharide esters have significant effects on neuroprotective and antioxidant systems.…”
Section: Resultsmentioning
confidence: 99%
“…1 H NMR (400 MHz, CDCl 3 ): δ H 5.53 (t, J = 10.0 Hz, 1H, H-3), 5.10 (t, J = 10.0 Hz, 1H, H-4), 4.97 (d, J = 3.6 Hz, 1H, H-1), 4.90 (dd, J = 10.0 and 3.6 Hz, 1H, H-2), 4.23 (dd, J = 12.0 and 4.4 Hz, 1H, H-6a), 4.14 (dd, J = 12.0 and 3.6 Hz, 1H, H-6b), 3.97-4.02 (m, 1H, H-5), 3.42 (s, 3H, OCH 3 ), 2. 21 Methyl 4-O-hexanoyl-2,3,6-tri-O-stearoyl-α-Dglucopyranoside (5): Oil. Yield 74%.…”
Section: Methodsmentioning
confidence: 99%
“…Many plant-based Oriental natural medicines are found to possess sugar esters with notable biological activities, and hence synthesis of such esters are of great interest over the past several decades [20,21]. However, sugars especially monosaccharide molecules contain several hydroxyl groups of similar reactivity and for this reason; selective acylation of monosaccharide derivatives is a prominent challenge in the field of carbohydrate chemistry.…”
Section: Introductionmentioning
confidence: 99%